1995
DOI: 10.1210/endo.136.8.7628369
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone directly affects the function of the different lobes of the rat prostate.

Abstract: In this study, we investigated the involvement of GH in rat prostate function. First, we demonstrated that specific transcripts corresponding to the GH receptor (4.5 kilobases) and to the GH-binding protein (1.2 kilobases) were expressed in the normal rat prostate, but also in all prostatic carcinoma cell lines tested (LNCaP, PC-3, MAT-Lu, MAT-LyLu, and Pif-1). Moreover, these transcripts were much more abundant in the human and rat carcinoma cells than in the normal tissue. One-year-old dwarf rats were supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 33 publications
1
2
0
1
Order By: Relevance
“…In this sense, as previous studies have indicated that the role of circulating GH in the PG is circumscribed to the stimulation of the local production of IGF1 , these data might also suggest the existence of an autocrine/paracrine GH/GHR loop potentially able to stimulate IGF1 production from the PG. Indeed, our results confirmed previous findings showing the expression of Igf1 , Igfr and Insr at the PG , and demonstrated the local expression of other components of the IGF1/insulin system such as various Igfbps ( Igfbp2 and Igfbp3 ) as well as of other associated proteins, as is the case of the glucose transporter Glut4 . Most importantly, as previously observed in other tissues , our results indicate that the expression pattern of the components of the GH, insulin and IGF1 regulatory axes can be finely modulated in the PG by environmental factors such as the diet.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this sense, as previous studies have indicated that the role of circulating GH in the PG is circumscribed to the stimulation of the local production of IGF1 , these data might also suggest the existence of an autocrine/paracrine GH/GHR loop potentially able to stimulate IGF1 production from the PG. Indeed, our results confirmed previous findings showing the expression of Igf1 , Igfr and Insr at the PG , and demonstrated the local expression of other components of the IGF1/insulin system such as various Igfbps ( Igfbp2 and Igfbp3 ) as well as of other associated proteins, as is the case of the glucose transporter Glut4 . Most importantly, as previously observed in other tissues , our results indicate that the expression pattern of the components of the GH, insulin and IGF1 regulatory axes can be finely modulated in the PG by environmental factors such as the diet.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, a growing body of evidence indicates that the endocrine axis comprising growth hormone (GH), insulin and insulin‐like growth factor 1 (IGF1) is locally expressed in the PG and plays a relevant role in its pathophysiology . Thus, earlier studies showed that pituitary‐produced GH is essential for PG development, controlling prostate size , and local expression of IGF1 and its receptor (IGF1R), in vivo and in vitro . IGF1 is a well‐known regulator of cell proliferation, differentiation and apoptosis , which is mainly produced by the liver , but is also expressed locally within the stromal and epithelial cells of PGs, where it can act as an autocrine/paracrine factor .…”
Section: Introductionmentioning
confidence: 99%
“…Human prostate cancer cell lines such as LNCaP and PC3 express GH receptors (GHRs) at levels greater than observed in normal tissue (25). Pollak et al (26) reported that the growth of androgen-independent PC3 cells is slowed in GHdeficient Little mice (Ghrhr lit/lit ) relative to control mice.…”
mentioning
confidence: 99%
“…Μέχρι στιγμής δεν ήταν γνωστό το αν η ανάπτυξη του προστάτη αδένα απαιτούσε τις ίδιες ουσίες. Ο Reiter και συνεργάτες κατόρθωσαν να παράσχουν σημαντικά στοιχεία για το ότι η GH είναι δυνατόν να διαδραματίζει κάποιο ρόλο στην ανάπτυξη του προστάτη, καθώς διεγείρει την παραγωγή του mRNA, τόσο του IGF-Ι, όσο και του υποδοχέα του σε αυτόν 134,135 . Το γεγονός ότι η δομή του προστάτη αδένα σε ζώα στα οποία είχε αφαιρεθεί το γονίδιο του IGF-Ι δεν ανακτήθηκε μέσω της χορήγησης GH είναι συμβατό με την αντίληψη ότι η ανάπτυξη του προστάτη και του μαζικού αδένα είναι παρόμοιες όσον αφορά στον καταρράκτη που ακολουθεί την επαγόμενη από την GH παραγωγή του IGF-Ι.…”
Section: Igfunclassified